Ion-specific interactions between halides and basic amino acids in water - Heyda, Jan; Hrobárik, Tomás; Jungwirth, Pavel (The journal of physical chemistry. A, 2009)
Ion specific behavior of halides at surfaces of aqueous basic amino acids is unraveled by means of molecular dynamics simulations employing both nonpolarizable and polarizable force fields. Analysis in terms of density plots, cumulative sums, and residence times provides a clear, robust, and quantitative picture of specific ion effects. Small anions like fluoride, but not heavier halides, exhibits strong affinity for positively charged groups in the order guanidinium > imidazolium > ammonium. In contrast, large soft anions such as iodide are weakly attracted to nonpolar regions of the amino acids. Because interactions of halides with positively charged groups exhibit a local character and are not overwhelmingly strong, similar behavior will be observed (in an additive sense) as well at surfaces of hydrated proteins.
Keywords: Amino Acids, Basic; Quaternary Ammonium Compounds; guanidin; Models, Molecular; jodidy; kvartérní amoniové sloučeniny; voda; chloridy; Ions; Iodides; Water; ionty; Guanidine; chemické modely; Chlorides; molekulární modely; aminokyseliny bazické; Fluorides; Bromine; imidazoly; Models, Chemical; brom; fluoridy; Imidazoles